2005
DOI: 10.1002/bdrb.20045
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of genes in fetal central nervous system after ethylnitrosourea administration

Abstract: The present study will provide a better understanding of the mechanisms of development, regeneration and carcinogenesis of the CNS as well as the mechanisms of ENU-induced fetal CNS injury and recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…, 2002, 2005a). Six hours after ENU treatment (injury phase), genes such as p21 Cip1/WAF1 , bax and mdm2 were up‐regulated in the fetal telencephalon (Katayama et al. , 2005b) explaining the cell cycle arrest that occurred.…”
Section: Resultsmentioning
confidence: 99%
“…, 2002, 2005a). Six hours after ENU treatment (injury phase), genes such as p21 Cip1/WAF1 , bax and mdm2 were up‐regulated in the fetal telencephalon (Katayama et al. , 2005b) explaining the cell cycle arrest that occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Ln[VEGF] pg/mg total protein. Logarithmic transformation of VEGF concentration values proliferative activity, changing the differentiation of the neuroepithelial progenitors cells from the subventricular plate during the neurogenesis/gliogenesis process (Katayama et al 2005b;Gil-Perotin et al 2006). Recently, using a similar model in rats, the same genetic alterations have been found as in secondary multiform glioblastomas in humans (Kokkinakis et al 2004).…”
Section: Vegf Expressionmentioning
confidence: 95%
“…Id proteins work to maintain NPCs in a proliferative state to recover the lost population. Katayama et al (2005b) also reported that the expression of osteopontin was prominently elevated in the recovery phase. Osteopontin is expressed in macrophages of the developing brain and contributes to their migration and phagocytic function (Choi et al, 2004).…”
Section: Repair Process Following Damage In Fetal Brainmentioning
confidence: 93%
“…Further, there has been a recent focus on regenera- tion of neural cells in the adult brain (Magavi et al, 2000;Doetsch, 2003;Picard-Riera et al, 2004). On the other hand, a few researchers have studied the repair period in the developing brain (Oyanagi et al, 1998;Kikuchi-Horie et al, 2004;Vaccarino and Ment, 2004;Katayama et al, 2005b), and, therefore, there is little information about how the repair or recovery process is regulated. Midkine (MK) is a heparin-binding growth factor that occurs as a product of a retinoic acid-inducible gene (Muramatsu, 1994).…”
Section: Repair Process Following Damage In Fetal Brainmentioning
confidence: 99%
See 1 more Smart Citation